Trypanosoma cruzi-infected pregnant women without vector exposure have higher parasitemia levels: implications for congenital transmission risk. - Victoria R Rendell; Robert H Gilman; Edward Valencia; Gerson Galdos-Cardenas; Manuela Verastegui; Leny Sanchez; Janet Acosta; Gerardo Sanchez; Lisbeth Ferrufino; Carlos LaFuente; Maria del Carmen Abastoflor; Rony Colanzi; et al. (PLoS ONE)
Background Congenital transmission is a major source of new Trypanosoma cruzi infections, and as vector and blood bank control continue to improve, the proportion due to congenital infection will grow. A major unanswered question is why reported transmission rates from T. cruzi-infected mothers vary so widely among study populations. Women with high parasite loads during pregnancy are more likely to transmit to their infants, but the factors that govern maternal parasite load are largely unknown. Better understanding of these factors could enable prioritization of screening programs to target women most at risk of transmission to their infants. Methodology/principal findings We screened pregnant women presenting for delivery in a large urban hospital in Bolivia and followed infants of infected women for congenital Chagas disease. Of 596 women screened, 128 (21.5%) had confirmed T. cruzi infection; transmission occurred from 15 (11.7%) infected women to their infants. Parasite loads were significantly higher among women who transmitted compared to those who did not. Congenital transmission occurred from 31.3% (9/29), 15.4% (4/26) and 0% (0/62) of women with high, moderate and low parasite load, respectively (χx2 for trend 18.2; p<0.0001). Twin births were associated with higher transmission risk and higher maternal parasite loads. Infected women without reported vector exposure had significantly higher parasite loads than those who had lived in an infested house (median 26.4 vs 0 parasites/mL; p<0.001) with an inverse relationship between years of living in an infested house and parasite load. Conclusions/significance We hypothesize that sustained vector-borne parasite exposure and repeated superinfection by T. cruzi may act as an immune booster, allowing women to maintain effective control of the parasite despite the down-regulation of late pregnancy.